(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article examines the conditions and features of the use of simulation innovation in small and medium-sized businesses (SMEs) in Uzbekistan. Indicators of the level of economic development of the regions are indicated.